Modification of gemcitabine with oxaliplatin in China for unresectable gallbladder cancer: a cost-effectiveness analysis - Zhaoyan Chen; Fangyuan Tian (Frontiers in Public Health)
BackgroundThe incidence of gall bladder cancer (GBC), one of the most prevalent bile duct malignancies, differs with ethnicity and geographic location. To treat unresected GBC in the Chinese setting, this study aimed to assess the financial effectiveness of a combination of modified gemcitabine and oxaliplatin.MethodsData from a randomized controlled study in which individuals with metastatic GBC were treated with oxaliplatin and gemcitabine demonstrated improved survival. A Markov model is built to calculate the incremental cost–benefit ratio (ICER) from the viewpoint of Chinese society on the basis of clinical symptoms and disease development. One-way certainty and probability sensitivity analyses are used to describe the uncertainty in the model.ResultsCompared with those of fluorouracil (FU) and folinic acid, the utility value of modified oxaliplatin combined with gemcitabine increased by 0.22QALY throughout the course of the 10-year simulation (FA). In a Chinese healthcare setting, the cost-effectiveness ratio (ICER) is $52765.59/QALY, with a 0% chance of cost–benefit at the WTP (willing-to-pay) level of $37697.00/QALY. The ICERs predicted by sensitivity analysis were not significantly affected by cost variations related to the management of Grade 3–4 AEs, the diagnostics used, or hospitalization expenditures.ConclusionIn a Chinese healthcare context, modified gemcitabine coupled with oxaliplatin (mGEMOX) is not a cost-effective treatment option for unresectable GBC.